Strategi promosi dalam meningkatan layanan di UPT Perpustakaan Proklamator Bung Karno Blitar pada masa pandemi - Ambarwati, Dwi; Handayani, Nurul Setyawati (Daluang: Journal of Library and Information Science, 2022)
Background. Promotion is the most important part of an organization to inform a product that is produced. The challenge is that special libraries need to promote services and collections so that users can also take advantage of during the Pandemic. The purpose of this research is to find out the promotion, strategy, and innovation used by UPT Bung Karno Library during the pandemic in improving its services.Methodology. This study uses qualitative methods. This study obtained data through interviews, observation, and documentation from informants who were taken by purposive sampling, then analysed them using descriptive analysis techniques.Results and discussion. The study can be seen that the UPT Bung Karno Proclaimer Library conducts promotions using social media, brochures, exhibitions, and socialization. In addition, the strategy used by Bung Karno's proclaimer UPT Library in promoting the library to the public focused more on Bung Karno's ideas and thoughts. How to improve services at the UPT Bung Karno Proclaimer Library by creating the "SILAKAN" program and creating the "ISU Karno" application which is used to access collections at the UPT Bung Karno Proclaimer Library.Conclusions. The Bung Karno Proclamator Library UPT has been working on promotions, strategies and innovations to improve its services during the pandemic, and carried out agitation so that it is hoped that more people will visit the library.